Memory and law - Nadel, Lynn.; Sinnott-Armstrong, Walter, 1955- (New York : Oxford University Press, 2012)
How well does memory work, how accurate is it, and can we tell when someone is reporting an accurate memory? Can we distinguish a true memory from a false one? Can memories be selectively enhanced, or erased? Are memories altered by emotion, by stress by drugs? These questions and more are addressed in this book.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Memory; Science and law